Efficient hydrodesulfurization of dibenzothiophene over core–shell Ni/Al2O3@SOD and Mo/Al2O3 composite catalysts. Issue 14 (6th June 2022) - Sun, Kun; Yang, Ge; Han, Jiaxin; Chai, Yongming; Li, Yanpeng; Wang, Chunzheng; Mintova, Svetlana; Liu, Chenguang; Guo, Hailing
Abstract : A DBT HDS reaction scheme based on different composite catalysts (Ni/Al2 O3 @SOD–Mo/Al2 O3 and Ni/Al2 O3 –Mo/Al2 O3 ) is proposed. Abstract : One composite catalyst, consisting of sulfur-tolerant Ni/Al2 O3 @SOD and MoS2 /Al2 O3, was developed for the hydrodesulfurization of dibenzothiophene. The sulfur-resistant Ni/Al2 O3 @SOD core–shell catalyst was prepared by coating a Ni/Al2 O3 core with a sodalite (SOD) shell via the gel hydrothermal method. The SOD shell ( d = 0.3 nm) can block the entry of the smallest sulfur-containing molecules (hydrogensulfide d = 0.36 nm) while allowing hydrogen molecules ( d = 0.29 nm) to diffuse to produce hydrogen spillover. With the excellent hydrogen spillover effect of the well-protected Ni, the composite catalyst (core–shell Ni/Al2 O3 @SOD–MoS2 /Al2 O3 ) showed high catalytic activity and selectivity of the direct desulfurization pathway in the hydrodesulfurization (HDS) of dibenzothiophene. Compared with the composite catalysts (Pt/Al2 O3 @SOD–MoS2 /Al2 O3 ) using noble metal Pt, the transition metal Ni composite catalyst exhibited broad hydrodesulfurization application prospects.